Dysphagia following cerebellar stroke: analyzing the contribution of the cerebellum to swallowing function - Hajipour, Masoume; Sobhani-Rad, Davood; Zainaee, Shahryar; Farzadfar, Mohammad Taghi; Khaniki, Saeedeh Hajebi (Frontiers in Neurology, 2023)
Swallowing is essential for human health, and the cerebellum is crucial for motor movement regulation. Cerebellar strokes may cause dysphagia, but their exact effects remain unexplored in swallowing function. Therefore, the aim of this study was to analyze the precise clinical characteristics of the oral and pharyngeal phases of swallowing after cerebellar stroke and to critically discuss the cerebellum’s contribution to swallowing. The study involved 34 participants with cerebellar strokes, gathered through convenience sampling. Neurologists diagnosed isolated strokes, and a speech and language pathologist examined swallowing ability using the Mann Assessment of Swallowing Ability. The study found that 52.9% of people experienced dysphagia after a cerebellar stroke. Dysphagia was significantly associated with a higher risk of aspiration. Age was also significantly correlated with dysphagia. No significant correlation was found between swallowing ability and sex. In conclusion, this study suggests isolated cerebellar stroke can adversely affect the motor and non-motor aspects of swallowing and cause severe dysphagia and aspiration risk. Thus, early diagnosis and timely management of dysphagia following a cerebellar stroke can help prevent serious consequences.